اثر استراتيجية فك التشفير الصوتي في اكساب المفردات اللغوية عند تلاميذ الصف الثاني الابتدائي بمادة القراءة - حسن محمد هادي (Journal of College of Education, 2018)
The research aims to know The effect of phonological deccoding strategy in the divergent results and thinking for the literal fourth class female students in Sociology ,and to achieve that the two zeros hypothesis were discussed . There is no statistical significant difference on the significant level (0,05) between the medium of marks for the experimental group students who study sociology according to the phonological deccoding strategy ,and the medium of marks for the disciplined group students who study the same subject according to the regular result’s test. This research focus on the literal fourth class students(Al-yusur high school of girls) at Al-kut city for the academic year 2015-2016 ,for the second course and for the last chapters of sociology subject .The researcher has used the experimental design with partial disciplined for the both groups(experimental and disciplined) of the post test for the collection test and divergent thinking. Al-yusur high school has been chosen intentionally to represent the sample of the research ,and randomly the both sections were chosen b-to represent the experimental group b-to represent the discipline group .